Strobilanthes mcgregorii, a replacement name for S. medocris (Bremek.) Y.F. Deng (Acanthaceae) - Deng, Yunfei (Phytotaxa, 2020)
When transferred Hemigraphis mediocris Bremekamp (1944: 107) to the genus Strobilanthes Blume (1826: 781, 796), I (Deng 2019) overlooked that the name Strobilanthes mediocris Benoist (1945: 8) has been used for another Malagasy species. According to the Art. 53.1 of International Code of Nomenclatural for Algae, Fungi and Plants (Shenzhen Code) (Turland et al. 2018), the name S. mediocris (Bremek.) Y.F. Deng is therefore a later illegitimate homonym and a replacement name is thus proposed below.